2020
DOI: 10.1007/s00417-020-04730-8
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial switch from aflibercept to ranibizumab for the treatment of refractory neovascular age-related macular degeneration

Abstract: The aim of this study was to evaluate the effects of switching to ranibizumab in patients with neovascular age-related macular degeneration (nAMD) refractory to aflibercept treatment and to identify predictive factors for switch response. Methods A retrospective chart review was conducted including 32 eyes from 26 patients with refractory nAMD, who switched from monthly intravitreal aflibercept treatment (≥ 6 months) to ranibizumab. Outcome measures included changes in visual acuity (VA), intraretinal fluid (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In total, 34% of eyes were noted to have an increase of 5 or more letters after the switch in therapy [73]. Other smaller, retrospective studies have demonstrated similar benefits when switching to IVR in a subset of eyes with eAMD unresponsive to IVA [74,75]. In addition, the more recently FDA approved IVBr offers an additional therapeutic option for anti-VEGF-resistant eAMD that has developed tachyphylaxis to other agents.…”
Section: Tachyphylaxis and Switching Anti-vegf Medicationsmentioning
confidence: 90%
“…In total, 34% of eyes were noted to have an increase of 5 or more letters after the switch in therapy [73]. Other smaller, retrospective studies have demonstrated similar benefits when switching to IVR in a subset of eyes with eAMD unresponsive to IVA [74,75]. In addition, the more recently FDA approved IVBr offers an additional therapeutic option for anti-VEGF-resistant eAMD that has developed tachyphylaxis to other agents.…”
Section: Tachyphylaxis and Switching Anti-vegf Medicationsmentioning
confidence: 90%
“…If, during the course of treatment, an anti-VEGF agent is found to be neither morphologically nor functionally effective without falling below its effective dose, a switch to another anti-VEGF agent may be appropriate. Several studies showed that switching to another anti-VEGF agent might lead to improvement in anatomical parameters and even stabilization or improvement of visual acuity [14][15][16][17]. For these switch patients, treatment is often initiated with a loading dose of three monthly injections, similarly as in treatment-naïve patients.…”
Section: Key Messagesmentioning
confidence: 99%
“…Although there are reports stating no significant difference between the anti-VEGF drugs ranibizumab and aflibercept, regarding the treatment response of IRC [ 29 ], one study has evaluated the effects of switching between the two [ 46 ]. The authors report that pre-switch structural changes on aflibercept negatively correlated with the post-switch response in morphological improvements to ranibizumab.…”
Section: Key Retinal Biomarkersmentioning
confidence: 99%
“…The authors report that pre-switch structural changes on aflibercept negatively correlated with the post-switch response in morphological improvements to ranibizumab. The absolute values of IRF at the point of the switch predicted the degree of response to switching to ranibizumab; thus the more IRF present prior to the switch, the better the eye responded to the switch [ 46 ]. Yet, post-hoc analysis of the VIEW studies highlights that fluid resolution was consistently greater for aflibercept treated 4-weekly compared to aflibercept treated 8-weekly or ranibizumab.…”
Section: Key Retinal Biomarkersmentioning
confidence: 99%